Pengembangan E Modul Monopoli Berbasis Project Based Learning (PjBL) Untuk Meningkatkan Literasi Sains Siswa SMP Negeri 11 Tapung - Azizah, Siti Nurul Laili; Agusminarti, Agusminarti; Hamka, Defrizal (Indonesian Research Journal on Education, 2026)
The process of developing a monopoly e-module based on project based learning (PjBL) to improve the secientific literacy of seventh grade students at SMP Negeri 11 Tapung on teh topic of ecology and biodiversity. The develompent follow the ADDIE (Analyze, Design, Development, Implementation, Evaluation). The product was validated by material and media experys, tested for practicality by teachers and tested on students. The validation results showed feasibility: material validation averaged 84% (very feasible) and media validation 96% (very feasible). Teasher practicality and student responses each scored 80% (interesting). The pre-test and psot-test results were 59,81% and 78,08% with an N-Gain of 0,44 (moderate).